The ghosts of Creakie Hall in funky phantoms - Wallace, Karen (London: Catnip, 2011)
Ghost-hunters have arrived at Creakie Hall. Miasma and Marmaduke, the family ghosts, are sure they're imposters who are up to no good. And when Miasma and Marmaduke are saving Creakie Hall from danger, things can get really hair-raising
Keywords: Children's stories